1999
DOI: 10.1007/bf03190359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein-calorie malnutrition on cytochromes P450 and glutathione S-transferase

Abstract: Protein-calorie malnutrition (PCM) can develop both from inadequate food intake and as a consequence of diseases such as cancer and AIDS. Several studies have shown that PCM can alter drug clearance but little information is available on the effect of PCM on individual cytochrome P450 isoforms and phase II conjugation enzymes. The aim of the present study was to begin a systematic evaluation of the effect of PCM on the activity of individual drug metabolizing enzymes in a rat model of PCM. Control and PCM rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…4; Table 1), potentially contributing to the increased anesthetic effects of KET in this rat group. Studies illustrating a PCM-related inhibition of P450s in rodents have been previously reported (Fernandez et al, 1996;Zhang et al, 1999). This inhibition includes the rodent counterparts of those reportedly associated with KET N-demethylation in humans (CYP2B, CYP3A, and CYP2C) (Yanagihara et al, 2001;Hijazi and Boulieu, 2002).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…4; Table 1), potentially contributing to the increased anesthetic effects of KET in this rat group. Studies illustrating a PCM-related inhibition of P450s in rodents have been previously reported (Fernandez et al, 1996;Zhang et al, 1999). This inhibition includes the rodent counterparts of those reportedly associated with KET N-demethylation in humans (CYP2B, CYP3A, and CYP2C) (Yanagihara et al, 2001;Hijazi and Boulieu, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Animal models of PCM have shown reductions in the clearance of doxorubicin (Cusack et al, 1992) and acetaminophen (Jung, 1985), and altered oxidative drug metabolism (Campbell and Hayes, 1974;Fernandez et al, 1996;Walter-Sack and Klotz, 1996;Zhang et al, 1999), conjugation (Zhang et al, 1999), and protein binding (Varma, 1979). PCM induced alterations in drug metabolism and disposition appear to be multifactorial processes (Anderson, 1988;Zhang et al, 1999), and a complete understanding of the effect of nutritional status on drug pharmacokinetics would be highly desirable for effective clinical treatment.…”
mentioning
confidence: 99%
“…[3][4][5][6] Many reports suggest that undernutrition, which is commonly prevalent in developing countries, may lead to changes in the activity of cytochrome P450-dependent mixed function oxidase [7][8][9][10] and it decreases the activities of CYP3A, CYP2C isoform. [11][12][13][14] Several pharmacogenetic studies have shown that genetic defects in drug-metabolizing enzyme of CYP2C9 affect phenytoin kinetics. [15][16][17][18][19] CYP2C9*2 and CYP2C9*3 are the two most common allelic variants that result in significant reduction in the metabolism of PHT.…”
Section: Introductionmentioning
confidence: 99%
“…The present study offered further support for a relevant role of Kupffer cells through the control of hepatocyte metabolism mediated liver injury. CYP3A contributed significantly to the biotransformation of xenobiotic chemicals such as drugs, and toxic chemicals [22] . GSTs constitute a multigene family of phase II conjugating enzymes broadly distributed phylogenetically.…”
Section: Discussionmentioning
confidence: 99%